An Aromatic Aldehyde Synthase Controls the Synthesis of Hydroxytyrosol Derivatives Present in Virgin Olive Oil - Rosario Sánchez; Lourdes García-Vico; Carlos Sanz; Ana G. Pérez (MDPI AG, 2019)
The phenolic composition of virgin olive oil (VOO) is strongly determined by the content and distribution of secoiridoid phenolic glucosides present in the olive fruit. Among them, oleuropein is the most abundant in olive mesocarp and is characterized by containing an hydroxytyrosol residue in its chemical structure. Hydroxytyrosol-containing molecules are those that exhibit the most important biological activities in virgin olive oil. In this regard, we identified an aromatic aldehyde synthase gene (OeAAS) from an olive transcriptome, which was synthesized, expressed in Eschrichia coli, and purified its encoded protein. The recombinant OeAAS is a bifunctional enzyme catalyzing decarboxylation and amine-oxidation reactions in a single step. OeAAS displays strict substrate specificity for l-DOPA to form 2,4-dihydroxyphenylacetaldehyde, the immediate precursor of hydroxytyrosol. In addition to the biochemical characterization of the enzyme, the expression analysis carried out in different olive cultivars and ripening stages indicate that OeAAS gene is temporally regulated in a cultivar-dependent manner. High correlation coefficients were found between OeAAS expression levels and the phenolic content of olive fruits and oils, which supports a key role for OeAAS in the accumulation of hydroxytyrosol-derived secoiridoid compounds in olive fruit and virgin olive oil.